Edukasi Intradialysis Exercise Pada Pasien dengam Hemodialisis - Santi Herlina; Mella Mahardika; Pricilia Dewi S; Dini Sholihatunnisa; Rizcha Aristiara; Rifdah Hasalah F; Dinda Nur Auliya; Afifah Afriana; Eka Ernawati; Murnis Sulis Tyaningsih (Prapanca : Jurnal Abdimas, 2023)
Chronic kidney disease is one of the health problems with the highest prevalence in the world. This condition occurs because the kidneys are no longer able to carry out their duties properly. To keep the patient's hemodynamics stable, temporary therapy is needed, namely hemodialysis. The hemodialysis process generally takes 4-5 hours, during the hemodialysis process a person is susceptible to muscle cramps, therefore intradialytic training is needed to be able to prevent and overcome if someone experiences cramps during the hemodialysis process. Based on the results of interviews with several patients, it was found that the patient had never received health education regarding muscle cramps and exercises to overcome them. The purpose of providing this education is to be able to increase the patient's knowledge, attitude, and practice in dealing with the problem of muscle cramps during hemodialysis. The target of this activity are patients at the Pandaoni Medika Hemodialysis Clinic, while this activity will be held in March 2023. The method used is lectures using leaflets and interactive demonstrations. Health education material includes cramps and intradialytic exercise steps. The results of the activity showed that the participants were able to take part in the exercises well, the participants enthusiastically took part in the exercises given which were shown by providing feedback in the form of questions about the exercises that had been taught so that in practice the knowledge that had been taught could be applied properly and was beneficial to patients.